2019
DOI: 10.1007/s11102-019-00943-1
|View full text |Cite
|
Sign up to set email alerts
|

Treatment adherence to pegvisomant in patients with acromegaly in Spain: PEGASO study

Abstract: Purpose. The burden of chronic daily subcutaneous administration of pegvisomant on adherence has not been previously studied. This study was aimed to determine the adherence to pegvisomant treatment in acromegaly patients in the real-world clinical practice setting in Spain. Methods. Multicenter, observational, descriptive, cross-sectional study in patients with acromegaly treated with pegvisomant for at least 12 months. Patient adherence was indirectly determined by Batalla and Haynes-Sackett questionnaires a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 28 publications
1
8
0
Order By: Relevance
“…Herein, we show the first real world data evaluating disease activity status using ACRODAT ® and its correlation with physicians' criteria, in a representative cohort of 111 Spanish patients attended in a clinical practice setting. Patient population was similar to other studies [27,28], with a mean age of 59.7 years and 51.4% of women. 60.7% of patients were controlled in terms of IGF-I and tumour volume.…”
Section: Discussionsupporting
confidence: 75%
“…Herein, we show the first real world data evaluating disease activity status using ACRODAT ® and its correlation with physicians' criteria, in a representative cohort of 111 Spanish patients attended in a clinical practice setting. Patient population was similar to other studies [27,28], with a mean age of 59.7 years and 51.4% of women. 60.7% of patients were controlled in terms of IGF-I and tumour volume.…”
Section: Discussionsupporting
confidence: 75%
“…No study assessing pegvisomant monotherapy reported AEs and no study examining pegvisomant at EDIs either as mono- or combination therapy reported on treatment-related deaths. Treatment adherence was higher at standard intervals compared with EDIs (n = 1 study), measured with the patient-reported Haynes-Sackett questionnaire, but it was unclear whether patients received pegvisomant combination therapy or monotherapy at the time the questionnaire was administered (Table 2 ) [ 39 ]. One patient-reported reason for lack of adherence to EDIs of pegvisomant was forgetfulness due to non-daily administration [ 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…This study reveals that the principal obstacle was the transportation of the pegvisomant (especially maintaining the cold chain during transportation) and anxiety about the injection. One third of patients made mistakes during the reconstitution (17%) and administration (22%) of pegvisomant [17].…”
Section: Adherencementioning
confidence: 99%